Photoluminescence of Eu(3+) ion in SnO(2) obtained by sol-gel - Morais, Evandro A.; Scalvi, Luis Vicente de Andrade [UNESP]; Tabata, Américo Sheitiro [UNESP]; Oliveira, José Brás Barreto de [UNESP]; Ribeiro, Sidney J. L. (Springer, 2008)
Photoluminescence data of Eu-doped SnO(2) xerogels are presented, yielding information on the symmetry of Eu(3+) luminescent centers, which can be related to their location in the matrix: at lattice sites, substituting to Sn(4+), or segregated at particles surface. Influence of doping concentration and/or particle size on the photoluminescence spectra obtained by energy transfer from the matrix to Eu(3+) sites is investigated. Results show that a better efficiency in the energy transfer processes is obtained for high symmetry Eu(3+) sites and low doping levels. Emission intensity from (5)D(0) -> (7)F(1) transition increases as the temperature is raised from 10 to 240 K, under excitation at 266 nm laser line, because in this transition the multiphonon emission becomes significant only above 240 K. As an extension of this result, we predict high effectiveness for room temperature operation of Eu-based optical communication devices. X-ray diffraction data show that the impurity excess inhibits particle growth, which may influence the asymmetry ratio of luminescence spectra.